Mechanism of Inflammation in Age-Related Macular Degeneration - Francesco Parmeggiani; Mario R. Romano; Ciro Costagliola; Francesco Semeraro; Carlo Incorvaia; Sergio D’Angelo; Paolo Perri; Paolo De Palma; Katia De Nadai; Adolfo Sebastiani (Mediators of Inflammation)
Age-related macular degeneration (AMD) is a multifactorial disease that represents the most common cause of irreversible visual impairment among people over the age of 50 in Europe, the United States, and Australia, accounting for up to 50% of all cases of central blindness. Risk factors of AMD are heterogeneous, mainly including increasing age and different genetic predispositions, together with several environmental/epigenetic factors, that is, cigarette smoking, dietary habits, and phototoxic exposure. In the aging retina, free radicals and oxidized lipoproteins are considered to be major causes of tissue stress resulting in local triggers for parainflammation, a chronic status which contributes to initiation and/or progression of many human neurodegenerative diseases such as AMD. Experimental and clinical evidences strongly indicate the pathogenetic role of immunologic processes in AMD occurrence, consisting of production of inflammatory related molecules, recruitment of macrophages, complement activation, microglial activation and accumulation within those structures that compose an essential area of the retina known as macula lutea. This paper reviews some attractive aspects of the literature about the mechanisms of inflammation in AMD, especially focusing on those findings or arguments more directly translatable to improve the clinical management of patients with AMD and to prevent the severe vision loss caused by this disease.